ChemInform Abstract: PdII‐Catalyzed Mild C—H ortho Arylation and Intramolecular Amination Oriented by a Phosphinamide Group. Issue 36 (9th September 2014) - Guan, Jing; Wu, Guo‐Jie; Han, Fu‐She
Abstract A novel method using phosphinamides as directing groups for the direct ortho‐arylation with arylboronic acids to produce mixtures of mono‐ and diarylated products is presented.